The Urgency of Establishing a Legal Regime for the Right of Publicity in Indonesia: A Study of Legal Politics and International Comparison - Hamonangan, Marcellius Kirana (Journal of Business, Management, and Social Studies, 2025)
This study investigates the urgency of establishing a dedicated legal regime for the Right of Publicity in Indonesia. It explores how the country’s fragmented regulatory landscape fails to adequately protect personal identity attributes such as name, image, and voice, especially in the face of AI, deepfakes, and the global digital economy. The primary research question is: How should Indonesia respond to the digital commercialization of identity through legal reform? This research employs a normative legal method supported by a legal-political framework, human rights theory, law and economics, and comparative legal analysis. It examines Indonesian laws, international instruments, and comparative frameworks from the United States and the European Union. The study finds that Indonesia lacks a coherent legal regime to protect the commercial use of personal identity. The existing protections across the Copyright Law, the Electronic Information and Transactions Law, and the Personal Data Protection Law are fragmented and insufficient. Comparative analysis reveals that while the U.S. treats the Right of Publicity as an economic right, the EU embeds it in personality and data protection laws. The paper advocates for regulatory reform to fill the legal vacuum. This paper provides a novel interdisciplinary approach by integrating legal politics and comparative law with human rights and economic theories. It uniquely proposes a hybrid model for Indonesia’s legal reform—drawing from both the U.S. and EU—while recommending a dedicated statute or integration into IP or PDP laws, supported by ethical guidelines, digital literacy campaigns, and a semi-independent regulatory body.